Whole genome sequencing reveals complex chromosome rearrangement disrupting NIPBL in infant with Cornelia de Lange syndrome - Duvdevani, Morasha Plesser (Am J Med Genet A, 2020)
Clinical laboratory diagnostic evaluation of the genomes of children with suspected genetic disorders, including chromosomal microarray and exome sequencing, cannot detect copy number neutral genomic rearrangements such as inversions, balanced translocations and complex chromosomal rearrangements (CCRs). We describe an infant with a clinical diagnosis of Cornelia de Lange syndrome (CdLS) in whom chromosome analysis revealed a de novo complex balanced translocation, 46,XY,t(5;7;6)(q11.2;q32;q13)dn. Subsequent molecular characterization by whole genome sequencing (WGS) identified twenty three breakpoints, delineating segments derived from four chromosomes (5;6;7;21) in ancestral or inverted orientation. One of the breakpoints disrupted a known CdLS gene, NIPBL. Further investigation revealed paternal origin of the CCR allele, clustering of the breakpoint junctions, and molecular repair signatures suggestive of a single catastrophic event. Notably, very short DNA segments (25bp, 41bp) were included in the reassembled chromosomes, lending additional support that the DNA repair machinery can detect and repair such segments. Interestingly, there was an independent paternally-derived miniscule complex rearrangement, possibly predisposing to subsequent genomic instability. In conclusion, we report a CCR causing a monogenic Mendelian disorder, urging WGS analysis of similar unsolved cases with suspected Mendelian disorders. Breakpoint analysis allowed for identification of the underlying molecular diagnosis and implicated chromoanagenesis in CCR formation.